Teknik Pengambilan Gambar (Angle) Dalam Memberikan Makna Dan Emosi Yang Disampaikan Pada Film Pendek Sabda Rindu - Akbar, Farhan Aidil; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In filmmaking, shooting techniques have a very important role in providing the meaning that you want to convey to the audience. Therefore, when making a film, it is necessary to take into account the size of the images when taking them so that the visuals displayed can please the audience's eyes and provide a message that is easy to understand. The cameraman is tasked with compiling, editing and reviewing images and is responsible for the production process from start to finish, then handed over to the editor. The cameraman himself carries out tasks starting from preparing the camera settings, checking the audio and adjusting the shooting angle because all the images and audio taken must be complete so as not to make it difficult for the editor to edit. The film Sabda Miss is a slice of life genre film where in this film, the cameraman tries to emphasize and emote the actors with the aim of bringing the audience to feel the emotions conveyed by the actors. In the production of the film Sabda Miss, the cameraman helps the director in visualizing the film script that has been provided by the script writer. There are several shooting techniques, one of which is close up. A close up shot itself is a shot from the top of the head to the neck, in one scene of the film Sabda Miss there are several techniques for taking close up shots. The cameraman tries to give an emotional impression of the actor so that the audience can be carried away by the actor's emotions. Therefore, the shooting techniques used in the film Sabda Missing are able to provide an attractive and professional film quality.